PENUNJUKAN PENJABAT KEPALA DAERAH DALAM SISTEM PEMERINTAHAN DEMOKRATIS - Afrianti, Firna; Umar, Kusnadi (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
The design of simultaneous national regional elections in 2024 has led to a vacancy in the position of regional head, to anticipate this, the government appoints an acting regional head to carry out the duties, functions, and authorities of the regional head until the inauguration of the definitive regional head. This research aims to analyze the application of democratic principles in the appointment of acting regional heads by using conceptual and statutory approaches. The process of appointing acting governors by the president and acting regents and mayors by the Minister of Home Affairs has ignored several fundamental principles such as the principle of free elections, equal political participation, accountability and transparency, protection of human rights (political rights), and the principle of placing officials with a merit system instead of a spoil system. The Constitutional Court in Decision Number 67/PUU-XIX/2021 has emphasized that the process of appointing acting regional heads must still be carried out democratically. The filling of acting regional heads also lacks strong social legitimacy because it does not involve active participation from the community.